Efficacy of the transurethral microwave coagulation therapy for recurrent bladder cancer with the flexible cystoscope - Kigure, Teruaki; Nakata, Kouki; Yuri, Yasuhiro (Journal of Microwave Surgery, 2012)
We have performed transurethral microwave tissue coagulation (MTC) for urinary bladder cancer, and especially applied MTC to small tumors of outpatients without anesthesia. In this report, flexible MTC (f-MTC) with a flexible cystoscope was performed. Ten patients of recurrent bladder cancer were treated. The tumor gradings were G1 and G2 in 4 and 6 cases. Six cases had solitary tumor and 4 cases had multiple tumors. In 8 cases, tumors were up to 3 mm in diameter, and 2 cases had tumors over 5 mm. Recurrence occurred in 3 cases. One case was followed by TUR-Bt and 2 cases were followed by f-MTC. This procedure is less painful and it can be performed immediately after cystoscopy. It was useful in the treatment of small bladder cancer.